A rare mimic of basal cell carcinoma. (11th November 2021) - Kamp, E.; Musbahi, E.; Graham, G.; Ascott, A.; Nardini, N.; Calonje, E.; Topham, E.
Abstract : Lymphoepithelioma‐like carcinoma of the skin is an extremely rare tumour whose aetiology is yet to be established. An 83‐year‐old female presented with a rapidly growing plaque on the chest wall diagnosed as lymphoepithelioma‐like carcinoma histologically. Click https://www.wileyhealthlearning.com/#/online-courses/f65512bf-449f-477f-abe9-0c494f12c085 for the corresponding questions to this CME article.